Anomalous Rapid Defect Annihilation in Self-Assembled Nanopatterns by Defect Melting - Kim, Bong Hoon; Park, So Jung; Jin, Hyeong Min; Kim, Ju Young; Son, Seung-Woo; Kim, Myung-Hyun; Koo, Chong Min; Shin, Jonghwa; Kim, Jaeup U.; Kim, Sang Ouk (AMER CHEMICAL SOC, 2015)
Molecular self-assembly commonly suffers from dense structural defect formation. Spontaneous defect annihilation in block copolymer (BCP) self-assembly is particularly retarded due to significant energy barrier for polymer chain diffusion and structural reorganization. Here we present localized defect melting induced by blending short neutral random copolymer chain as an unusual method to promote the defect annihilation in BCP self-assembled nanopatterns. Chemically neutral short random copolymer chains blended with BCPs are specifically localized and induce local disordered states at structural defect sites in the self-assembled nanopatterns. Such localized defect melting relieves the energy penalty for polymer diffusion and morphology reorganization such that spontaneous defect annihilation by mutual coupling is anomalously accelerated upon thermal annealing. Interestingly, neutral random copolymer chain blending also causes morphology-healing self-assembly behavior that can generate large-area highly ordered 10 nm scale nanopattern even upon poorly defined defective prepatterns. Underlying mechanisms of the unusual experimental findings are thoroughly investigated by three-dimensional self-consistent field theory calculation.
Keywords: BLOCK-COPOLYMER FILMS; LINE PATTERNS; THIN-FILMS; NANOLITHOGRAPHY; LITHOGRAPHY; TEMPLATES; SOLVENT; ARRAYS; NANOSTRUCTURES; GRAPHOEPITAXY